2020
DOI: 10.7717/peerj.9861
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of dimethylsulfoniopropionate (DMSP) demethylation enzyme DmdA in marine bacteria

Abstract: Dimethylsulfoniopropionate (DMSP), an osmolyte produced by oceanic phytoplankton and bacteria, is primarily degraded by bacteria belonging to the Roseobacter lineage and other marine Alphaproteobacteria via DMSP-dependent demethylase A protein (DmdA). To date, the evolutionary history of DmdA gene family is unclear. Some studies indicate a common ancestry between DmdA and GcvT gene families and a co-evolution between Roseobacter and the DMSP-producing-phytoplankton around 250 million years ago (Mya). In this w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…In contrast, Rhodobacterales was positively associated with S-containing formulas and relative labile protein-like C1 component and negatively associated with MLB R . This fits well with previous findings demonstrating links between members of the Rhodobacteraceae family and sulfur metabolites (47,72), but it also suggests that Rhodobacterales might be less competitive when the substrates are relatively more recalcitrant. Glucose assimilation results in biomass and energy production but also in the synthesis of other metabolic intermediates (e.g., amino acids and fatty acids) needed for bacterial growth (73,74).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, Rhodobacterales was positively associated with S-containing formulas and relative labile protein-like C1 component and negatively associated with MLB R . This fits well with previous findings demonstrating links between members of the Rhodobacteraceae family and sulfur metabolites (47,72), but it also suggests that Rhodobacterales might be less competitive when the substrates are relatively more recalcitrant. Glucose assimilation results in biomass and energy production but also in the synthesis of other metabolic intermediates (e.g., amino acids and fatty acids) needed for bacterial growth (73,74).…”
Section: Discussionsupporting
confidence: 92%
“…The success of Alteromonadales in utilizing glucose could be due to the phosphoenolpyruvate carboxylase strategy in Gammaproteobacteria instead of the pyruvate carboxylase in Alphaproteobacteria (44), giving them a competitive advantage. In contrast, the degradation of the more complex GBT and DMSP substrates requires specific transporters and enzymes (e.g., betaine-homocysteine methyltransferase and DMSP-dependent demethylase A protein), resulting in the dominance of Alphaproteobacteria (mostly Rhodobacteraceae) with a smaller contribution of the Gammaproteobacterial members (45)(46)(47). Previous studies have also shown that Alphaproteobacteria can account for up to 30% of total bacteria assimilating DMSP in natural environments (48).…”
Section: Discussionmentioning
confidence: 99%
“… 7 Nearly all known DMSP-catabolizing bacteria belong to the phylum Proteobacteria with dmdA , and dmdA gene could be transferred horizontally in marine Gammaproteobacteria. 34 However, few studies have reported that bacteria have mutations in dmdA genes. Thus, the effect of dmdA gene mutation on E. coli needs to be further explored in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Protein prediction was performed with Prodigal 39,63 . The taxonomic identity of predicted proteins was obtained using EUKulele v2.0.3 19 , first using a combined database containing the MMETSP 27,29,36 , MarRef 64 , and additional Phaeocystis references, including the genome resources for Phaeocystis antarctica and Phaeocystis globosa 65,66 available from the IMG/M (Integrated Microbial Genomes & Microbiomes) database (Phaant1 and Phaglo1, respectively), Phaeocystis cordata, Phaeocystis jahnii, and Phaeocystis globosa transcriptome resources [67][68][69] , and a Phaeocystis pouchetii transcriptome (Mars Brisbin et al in prep). The contigs associated with the proteins identified to the genus Phaeocystis were quantified against the raw reads using the CoverM software in contig mode (v0.6.2; https://github.com/wwood/CoverM; coverm contig --min-covered-fraction 0).…”
Section: Genus Scale: Tara Oceans Metagenomesmentioning
confidence: 99%